Association of gut microbiota dietary index with metabolic dysfunction-associated steatotic liver disease: the mediating roles of inflammation and body mass index - Pu, Yu; Tan, Zongbiao; Wu, Yanrui; Zeng, Suqi; He, Haodong; Zhang, Jixiang; Dong, Weiguo (Frontiers in Nutrition, 2025)
BackgroundThe gut microbiota plays a significant role in the progression of Metabolic Dysfunction-Associated Steatotic Liver Disease (MASLD). The recently introduced Dietary Index of Gut Microbiota (DI-GM), which reflects the diversity of the gut microbiota, has yet to be investigated in relation to MASLD.MethodsThis analysis used raw data from the National Health and Nutrition Examination Survey (2001–2018). MASLD was identified using the US-Fatty Liver Index (US-FLI), and dietary recall data were applied to calculate the Dietary Index of Gut Microbiota (DI-GM). Weighted multivariate logistic regression models assessed the relationship between DI-GM and MASLD. Additionally, mediation analysis was performed to evaluate the influence of high-sensitivity C-reactive protein (hs-CRP) and body mass index (BMI) on the relationship between DI-GM and MAFLD. Propensity score matching (PSM) was employed to minimize confounding and reduce bias inherent to observational studies.ResultsA total of 3,473 participants were included in the analysis, among whom 1,247 were diagnosed with MASLD, with a weighted prevalence of 35.90%. After adjusting for demographic, lifestyle, and metabolic syndrome-related variables, a higher score of DI-GM was strongly linked to a lower risk of MASLD (OR = 0.90, 95% CI: 0.85–0.95, p < 0.001). Mediation analysis estimated that BMI accounted for 59.47% of the association (p < 0.001), while hs-CRP explained 15.68%. Even after PSM, a higher score of DI-GM remained significantly associated with a lower incidence of MASLD.ConclusionThe newly proposed DI-GM demonstrated a notable negative correlation with the prevalence of MASLD. Mediation analyses revealed that this relationship was largely influenced by BMI and hs-CRP, highlighting their critical mediating roles.